2020
DOI: 10.3390/vetsci7020059
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity in Goats Exposed to Arsenic in the Region Lagunera, Northern Mexico

Abstract: The Region Lagunera, a region in northeast Mexico, is undergoing significant problems with the quality of its groundwater, which exceeds the permissible limits of contaminants and/or heavy metals stipulated in Mexican legislation. The present study evaluated chronic toxicity in male goats exposed to arsenic via one ex situ Group 1 (n = 5) and one in situ female goats Group 3 (n = 10). The treatment in Group 1 was carried out in the La Laguna experimental field of the Instituto Nacional de Investigaciones Fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Exposed groups received arsenic in drinking water 1 mg/L of arsenic (As 2 O 3 ; Sigma Aldrich, St. Luis Missouri, USA) equivalent to 1 ppm, for an interrupted period of 16 weeks, and the control groups received non-As-contaminated water to drink ad libitum. The arsenic dose used in this study was a midpoint based on the highest concentrations of As in drinking water recorded around the world (500–2040 µg/L) 109 111 . Furthermore, this dose of arsenic trioxide has been one of the lowest doses recorded, where reproductive abnormalities are shown in males 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Exposed groups received arsenic in drinking water 1 mg/L of arsenic (As 2 O 3 ; Sigma Aldrich, St. Luis Missouri, USA) equivalent to 1 ppm, for an interrupted period of 16 weeks, and the control groups received non-As-contaminated water to drink ad libitum. The arsenic dose used in this study was a midpoint based on the highest concentrations of As in drinking water recorded around the world (500–2040 µg/L) 109 111 . Furthermore, this dose of arsenic trioxide has been one of the lowest doses recorded, where reproductive abnormalities are shown in males 38 .…”
Section: Methodsmentioning
confidence: 99%
“…This investigation should aim to assess the contribution of As intake from these sources, as well as its potential effects on the population. Furthermore, farm animals exposed to As through contaminated drinking water and feed materials could suffer adverse health effects 73 , highlighting the need for further investigation in this area.…”
Section: Discussionmentioning
confidence: 99%
“…This semi-arid area is one of the hotspots of groundwater arsenic contamination in the world, and elevated levels of arsenic have been reported in this area. Our previous study reported high levels of drinking water arsenic in this region, ranging from 20.6 to 709.3 µg/L [ 31 ]. Therefore, the residents in this area were considered as potentially exposed to high concentrations of arsenic from their drinking water.…”
Section: Methodsmentioning
confidence: 99%